Consumul de apă – indicator al calității vieții - Humă, Cristina (Calitatea Vieții, 2015)
The paper aims to highlight the importance of both quantity and quality of water for the quality of human life. Therefore, the different functions of water, especially for domestic, agricultural and industrial use, were shown in various geographical regions of the world, and in Romania either. In this regard, some indicators related to water consumption for agricultural, industrial and domestic purposes were used, at the state level. With respect to water for domestic consumption, the way of getting water to households was mainly considered, focusing on people’s access to drinking water in the home, and on water consumption per capita. The situation of the outlined indicators was taken into account primarily in Romania, by comparing it with other European countries. The importance in terms of water quality was highlighted by the effect on human health of the water consumption, supplied either publicly or from individual sources. The analysis conducted was based on estimates and statistical data available at international, European and national level. The work also considered the legal framework on the drinking water for domestic purposes in Romania and in the European Union, which aimed at ensuring the quality of drinking water, in order to maintain human health.